Louping Ill Virus Outbreak in North-East Wales. Issue 10 (20th December 2019) - Dorey-Robinson, Daniel; Folly, Arran; Phipps, Paul; Vidana, Beatriz; Holmes, Paul; Johnson, Nicholas
Abstract : The disease louping ill is an encephalitic viral infection that is fatal in sheep (Oves aries) and grouse (Lagopus lagopus). The disease is caused by the louping ill virus (LIV) and transmitted by sheep ticks (Ixodes ricinus) in upland areas of the United Kingdom. Reported outbreaks are sporadic and prevention is mainly targeted at controlling the vector. Despite the implications for animal welfare and the rural economy, research on the epidemiology and control of LIV has been neglected in recent years. In April of 2019, a group of 200 yearling ewes were moved onto hill grazing at a farm near Oswestry on the English/Welsh border. Within 2-3 weeks, ten had developed clinical signs suggestive of neurological impairment, including torticollis, fitting, head shaking and recumbency. A number of the affected ewes were later found dead. Following post mortem, histopathological investigation of brain tissue from an affected ewe, which had undergone euthanasia, detected glial nodules and perivascular cuffing indicating subacute non-suppurative encephalitis. The haemagglutination inhibition serological test was positive and provided evidence for infection with LIV. Reverse transcription polymerase chain reaction (RT-PCR) gave a positive result for samples of the hind brain and the resulting sequence confirmed the presence of LIV. Phylogenetic analysis indicated that the virus showed the highest identity (>99%) with LIV sequences from Aberystwyth in west Wales and was distinct from other LIV isolates found in the north of England. This case study highlights the ongoing threat to UK sheep from LIV.